RE-writing the Pain: A Lyric Essay - Noble, Helen Jane; Cole, Beverly (European Journal for Qualitative Research in Psychotherapy, 2020)
The creative, non-fiction approach of ‘lyric essay’ is used to flesh out my heuristic experience. My essay builds on some earlier heuristic research conducted about my experience, over a lifetime, of musculoskeletal pain. That research questioned whether suffering is a conscious choice, even if pain is inevitable. This lyric essay – utilizing a mosaic of critical review, description, metaphor and montage - is a phenomenological reflection on my process of writing the pain which strives to better convey a palpable sense of my embodied experience of pain and bodily alienation. Following a literature review and an exploration of the nature of lyric essays, a personal narrative and critical discussion evaluates how my experience of the writing process, and the use of lyric essays, may contribute to the field of psychotherapy. As a raw, impromptu, reflective account of pain across the life span, the essay contains a detailed snapshot of my lived experience. It contrasts how a child relates to negative experiences, and how an adult, trained in psychotherapy, might choose to process her emotions. The approach of lyric essays is offered as an in-depth way to explore therapists’ own experience and that of their clients.